Cross Cultural Issues in Business Communication : An Analysis of Finland Based Business Professionals’ Cultural Intelligence in the Indian Environment - Kumar, Manoj (2021)
Businesses across the world are continuously expanding their boundaries in different countries. These businesses require talents who are skilled at cross-cultural communications. Cultural intelligence allows professionals to adapt, learn and be creative in a foreign environment. To assess the individuals’ cultural intelligence capabilities various theories are available. One of the most popular theories to measure cultural intelligence capabilities is the CQ theory. CQ theory provides a four-factor model including Motivational CQ, Cognitive CQ, Metacognitive CQ, and Behavioral CQ. These dimensions facilitate an individual to utilize their cultural intelligence in multicultural settings.